Kontribusi Teori Behavioristik Dalam Pembelajaran - Sokip, Sokip (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
Education is a means of changing something into a better thing with a certain period of time. Especially, education is a learning process which until now can still be found that the instructors who deliver material to students without understanding what learning approaches are being used. This is the basis of the teaching process in the classroom and refers to the goals and targets of the learning process itself. One of these approaches is behavioristic or giving stimuli to get feedback from students. This study aims to find clarity about how important the behavioristic approach is applied in classroom learning. Moreover in answering the existing formula, the researcher uses the library research method to find out how the contribution of teaching with the behavioristic approach. The result includes (1) contributions in analyzing student character; (2) media development and teaching strategies; (3) the formation of confidence in students.